2019
DOI: 10.1007/s00405-019-05466-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 255 tracheostomies in an otorhinolaryngology-head and neck surgery tertiary care center: a safe procedure with a wide spectrum of indications

Abstract: Purpose To review indications, patient characteristics, frequency, and safety for surgical tracheostomies performed by otolaryngologist-head and neck surgeons in a single tertiary care center. Methods Surgical tracheostomies performed by otolaryngologist-head and neck surgeons at Helsinki University Hospital between January 2014 and February 2017 were retrospectively reviewed. Patient demographics, surgical data, and peri- and postoperative mortality information were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The late complications after airway management in AE or AS need evaluation in future studies, as known late complications of tracheotomy and intubation include for example tracheal stenosis [17, 18] and tracheocutaneous fistula after tracheotomy [19], and laryngeal granulomas and arytenoid cartilage dislocation after intubation [20, 21]. Our recent study reported surgical mortality to be 0.4% in all tracheotomized patients ( n = 255) in our department, with AE or AS comprising only seven of indications for the procedure [22].…”
Section: Discussionmentioning
confidence: 99%
“…The late complications after airway management in AE or AS need evaluation in future studies, as known late complications of tracheotomy and intubation include for example tracheal stenosis [17, 18] and tracheocutaneous fistula after tracheotomy [19], and laryngeal granulomas and arytenoid cartilage dislocation after intubation [20, 21]. Our recent study reported surgical mortality to be 0.4% in all tracheotomized patients ( n = 255) in our department, with AE or AS comprising only seven of indications for the procedure [22].…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the most common indication for tracheotomy was simultaneous surgery for head and neck cancer (50.5%), which is comparable to studies evaluating surgical tracheostomies performed specifically by otolaryngologists reporting 57.6% and 45%. 3 , 21 Though these patients comprised the largest subset of our population, it should be noted that this cohort is a markedly heterogeneous population with all the implications that entails. The effects of the heterogeneity of this population can be seen in the ED readmission rates reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 Complications with higher mortality rates in the intra-operative and early postoperative period include pneumothorax, hemorrhage, accidental decannulation and false passage, mucus plug, whereas, pneumonia and infections are typically less severe. [1][2][3][4] Late postoperative complications include subglottic stenosis, tracheal stenosis, tracheocutaneous fistula, tracheoesophageal fistula, tracheoinnominate artery fistula, accidental decannulation, and infection. [4][5][6][7] Studies have reported that complications occur in 5%-40% of tracheostomies, but the vast majority are minor.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the risk of bleeding and infection, which comprises both pneumonia or wound infection, other adverse events have been reported. These include secondary sinusitis, pneumothorax, subcutaneous emphysema, and persistent damage of the tracheal cartilage [ 77 ]. The one-year overall survival after tracheotomy in a mixed population in need for airway assistance (both neurological intensive care unit and HNC population) was 50% [ 78 ].…”
Section: Oropharyngeal Dysphagia In Head and Neck Cancermentioning
confidence: 99%